(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
India is homebound owing to the corona virus disease 2019 (COVID-19) pandemic. The loss inlearning in pandemic is estimated to be up to 50 of the expected academic level. The impact could belifelong and likely to be most significant for the disadvantaged and marginalized children. The impact ofpandemic (COVID-19) has been observed in every sector all over the world. The education sector inIndia as well as the world is largely affected by this. It had enforced worldwide lockdown creating alot of challenges to the students’ life. Around 32 crore learners were effected and they couldn’t attendcollegesschools and all educational activities halted. The outbreak of COVID-19 has taught us that changeis inevitable. It has worked as a catalyst for the educational institutional to grow and adopt technologybased platforms of digital learning that have not been used before. There has been a shift fromtraditional methods of teaching and learning to online learning. This study is aimed at depicting theimpact of COVID-19 on student learning and associated opportunities, barriers and outcomes ofthe pandemic. The main concerns of this paper are to find out both positive and negative aspects of thepandemic on student learning in addition to suggesting some remedial measures. It unfolds thedifficulties encountered while using online learning platforms, skills developed while studyingduring pandemic, interaction and communication with teachers, students’ opinion on online educationconsidering the experience during Covid-19 pandemic as well as the satisfaction of the learnerswith present way of teaching (i.e online mode). It also recognizes the perceived advantages anddisadvantages of online education. For achieving the purpose of this study, questionnaire made inGoogle forms was used. The data was collected from students of University of Jammu, Union Territory ofJK, India, by simple random sampling.